Differentiated treatment of multi-resistant Gram-negative pathogens in intensive care units - Schmoch, Thomas; Heininger, Alexandra; Richter, Daniel; Brenner, Thorsten; Weigand, Markus A. (Anästhesiologie & Intensivmedizin, 2021)
Multi-resistant Gram-negative pathogens will pose an enormous challenge to medicine in the coming years. Therefore, the World Health Organization emphasises that there is a great need for the development of new antimicrobial drugs. At the same time, intensivists must be prepared to treat complex infections with multi-resistant pathogens more often. As a consequence, a sound knowledge of the resistance mechanisms and the available antimicrobial drugs is essential. In this context, new beta-lactam antibiotics (and combinations), such as ceftolozane / tazobactam or ceftazidime / avibactam, but also the combinations of / with meropenem / vaborbactam, aztreonam / avibactam or imipenem / cilastatin / relebactam, should be mentioned. Their availability is to be welcomed, especially with regard to their reduced toxicity in comparison to colistin-based therapies. Moreover, this review comments on cefiderocol, a new drug which could revolutionise the treatment of multi-resistant Gram-negative germs. This review article intends to give the reader an overview of the resistance mechanisms prevalent in Germany and the respective appropriate treatment options.
Gesehen am 03.11.2021